Skepticism Over Scores: Investigating the Relationship Between Academic Performance and Financial Misstatement Detection - Juanda Astarani (Jurnal Ilmiah Akuntansi, 2025)
This study examines the relationship between academic performance indicators and accounting students' ability to detect misstatements in financial statements, exploring whether traditional educational metrics effectively predict real-world fraud detection capabilities. The research employed a quantitative cross-sectional survey design using data from thirty-two accounting students who completed auditing courses. Data collection utilized structured questionnaires through digital platforms, measuring academic achievement through grade point averages and course-specific performance alongside misstatement detection abilities assessed through comprehensive case studies. Multiple regression analysis was applied to examine relationships between variables, with statistical testing including normality and multicollinearity assessments. Results revealed no significant relationships between academic performance measures and detection capabilities, with the combined model explaining minimal variance in outcomes. These findings challenge conventional assumptions that higher academic achievement translates to superior fraud detection skills, highlighting a critical gap between academic evaluation methods and practical professional competencies. The study emphasizes the need for curriculum reform integrating professional skepticism, forensic accounting principles, and experiential learning approaches to better prepare students for identifying financial irregularities in professional practice.